Infrastructure investment, disruption, and tourism response : short-run associations of infrastructure across New Zealand’s regions : a thesis submitted in fulfilment of the requirements for the degree of Master of Business Studies (Economics), Massey Business School, Massey University, Albany, Auckland, New Zealand - Sabharwal, Rohit (Massey University, 2025)
This thesis examines the short-run association between infrastructure investment and regional tourism outcomes in New Zealand. While existing research has largely focused on individual infrastructure sectors, particularly transport, relatively little work has examined multiple infrastructure categories within a unified empirical framework or explored these relationships at the regional level in a small, high-income economy. This study addresses that gap by analysing how different forms of infrastructure investment are associated with tourism activity across New Zealand’s sixteen regions. The empirical analysis draws on a region-year panel dataset combining three dimensions: regional economic and demographic conditions, infrastructure capital expenditure across transport and energy sectors, and measures of tourism activity. This structure allows the analysis to exploit both cross-regional variation and temporal dynamics, while remaining attentive to the constraints imposed by short and uneven regional time series. Methodologically, the study adopts a parsimonious dynamic panel specification estimated over the pre-pandemic period from 2012 to 2019. The model focuses on short run adjustments in tourism activity, measured by changes in commercial accommodation guest nights, while controlling for persistence, lagged infrastructure investment, regional economic conditions, and common year-specific shocks. Given data limitations and the observational nature of the setting, the analysis is descriptive in nature and does not seek to identify causal effects. The results indicate that short-run associations between infrastructure investment and tourism outcomes are modest and heterogeneous across infrastructure categories. Airport capital expenditure exhibits a negative but statistically imprecise association with guest nights at a one-year horizon, consistent with temporary disruption during major airport upgrade cycles. At the same time, airport investment is positively associated with international tourism electronic card spending, suggesting that improvements may be linked to shifts in visitor composition or spending intensity rather than immediate increases in visitor volumes. Public transport investment is negatively associated with short-run international tourism expenditure, while road and energy infrastructure display limited and statistically imprecise associations within the same time frame. Robustness checks using alternative specifications yield qualitatively similar patterns but highlight sensitivity to model structure and functional form. Overall, the findings emphasise the timing-dependent and category-specific nature of infrastructure-tourism relationships in New Zealand. Rather than generating uniform or immediate tourism gains, infrastructure investment appears to interact with tourism activity through transitional dynamics and sector-specific channels. These results underscore the importance of cautious interpretation when evaluating short-run tourism responses to infrastructure investment and highlight the need for longer time horizons and richer data to assess longer-term impacts.
Keywords: Infrastructure investment; regional tourism; panel data; tourism economics; New Zealand; 350899 Tourism not elsewhere classified; 380116 Tourism economics